KAJIAN PENGEMBANGAN EKSPOR KAYU LAPIS INDONESIA KE JEPANG - Kirsfianti L Ginoga; Rachman Effendi (Jurnal Penelitian Hasil Hutan, 1989)
Precently  non-oil   export   development     is  very   important    for  Indonesia's   economy.    This  study   is  to  analize, Indonesia's   plywood   export   development,   in particular   to  Japan,  and  to  discuss  some  factors   which  are supposed   to influence   it.In  line with  the  fast growth  of plywood  industry   in Indonesia  there  is diversification   of  export   markets.  Plywood export   to Japan  goes  on  to increase, and  now  80%  of  the Japan's  total plywood  import  come  from  Indonesia.The  result   of  this study  shows  that market  potential of Indonesia's  plywood  to Japan large enough,  especially  if it is perceived   from  the number  of population   of age 15 years and  up  (Xl),   where  the regression  coefficient   has shown   that each increase of  1000   people   in the population  of age 15 years and up would  increase the Indnoesia 's plywood  export  for around  50 m3.  But  there is some  c;on~traints which suppress  the market  potential,   among  other  things are Japan's plywood production,    consumers  preference   and government's   protective  policy.   The  market  share of Indonesia's   to Japan  can be increased  if  the  constraints   are relaxed.